Asimetri Informasi dan Cost of Equity Capital - Puput Tri Komalasari; ZAKI BARIDWAN (The Indonesian Journal of Accounting Research, 2013)
This research examines the association between an information asymmetry and cost of equity capital. The conventional wisdom, it is generally assumed that a  company which has a disclosure at a greater extent will reduce the cost of equity capital.  An empirical research indicated more disclosure will reduce information asymmetri. This research tries testing if the declining of information asymmetry resulting from the extent of disclosure will bring the effects on declining of the cost of equity capital. Further, the research tries testing the differences of declining level of cost of equity capital as a result of  the declining of information asymmetry among relatively small companies and large companies.The number of  companies taken as samples in the research cover about 213 companies, listed at Jakarta Stock Exchange before 1996. The hypothetical test was conducted by implementing cross-sectional method, taking a research periode of 1996. This research adopts Bid ask spread as a basis for measurement of  information asymmetry and capital asset pricing model (CAPM) used to estimate the quantity of cost of equity capital. In order to control the size effects, analytical model in the research also utilizes the variables of  market values of equity.As expected, the research showed up the existence of a positive relationship between information asymmetry and cost of equity capital. A controlled-variable, NPSR, also brought effects on the number of cost of equity capital significantly.  This fact makes it possible to separate the hypothesis between a large company and a small one.Separately, the results of testing between small scaled - companies and large scaled-companies indicated real differences at the declining level in term of cost of equity capital. Large companies experience a greater declining cost of equity than small companies, therefore, a large company earned a greater benefit resulting from a greater disclosure, compared from  a small company. This results implied  that the companies have to improve the quality of their disclosure with the intention that the information asymmetry happening among the market players will declines and so will the cost of equity capital.